Two prehistoric short-cists and an early medieval long-cist cemetery with dug graves on Kingston Common, North Berwick, East Lothian - Suddaby, Ian; Duffy, Paul; Jackson, Adam; Lawson, John; MacSween, Ann; Warren, Graeme; Mudie, George; Hicks, Kevin; Whitelaw, Leeanne (Scottish Archaeological Internet Reports, 2009)
Human remains were discovered during the laying of a water pipe to service the refurbished Fenton Tower at Kingston, near North Berwick (NGR: NT 544 823), in 2001. Two short-cist burials, thirty-eight long-cist burials and bank-defined terraces containing dug graves and a possible chapel (NT58SW 152) were found. It is suggested that three main periods of burial are represented, spanning the Neolithic to the early 2nd millennium AD.